The Influence of Work Culture and Work Environment on Teacher Performance at SMPN 6 Karawang - Tiara Elza Listama; Sari Marliani; July Yuliawati (Economics and Digital Business Review, 2025)
This study aims to determine , analyze and explain the influence of work culture and work environment on teacher performance at SMPN 6 West Karawang. This study uses a quantitative method with a descriptive and verification approaches . The study population consisted of 50 teachers and all were sampled with a saturated sampling technique . Data were collected through questionnaires , analyzed using multiple linear regression methods using SPSS version 26. The results of the descriptive analysis indicate that work culture , work environment and teacher performance are in the very good category . The results of the t- test with a significance value of 0.000 <0.05, t- count of work culture 12,649 and work environment 11.197> t- table 2.012, that work culture and work environment have a positive and significant effect on teacher performance . The results of the f- test with a significance value of 0.000 <0.05, f- count 208.096> f- table 3.195 that work culture and work environment together have a significant positive effect on teacher performance . The coefficient of determination (R²) of 0.899 indicates that 89.9% of teacher performance is influenced by work culture and work environment , while 10.1% is influenced by other factors not examined . The conclusion of this study is that improving teacher performance can be achieved through a positive work culture and a comfortable and supportive work environment . This study provides a practical contribution to schools as a basis for formulating policies in efforts to improve teacher performance .